Iphone Marketing Strategy On The Level Of Iphone Sales In Labuhanbatu Selatan Society - Ade Parlaungan Nasution; Pristiyono Pristiyono; Nurhamidah Nurhamidah (Jurnal Mirai Management, 2023)
This study aims to examine the influence of the marketing strategy of a sugar business on the level of sales of brown sugar businesses through online marketing I phone in Labuhanbatu Selatan. Data collection was carried out by distributing questionnaires and distributing them to 100 research samples, namely user I phone. Data analysis in this study uses the help of smart pls. Data testing techniques performed on partial and simultaneous testing. The results of the analysis show that overall the independent variables have a positive and significant influence on the dependent variable.